Climate Responses to Tambora‐Size Volcanic Eruption and the Impact of Warming Climate - Yang, Linshan; Gao, Yujuan; Gao, Chaochao; Liu, Fei (Geophysical research letters, 2022)
The climatic consequences of large volcanic eruptions depend on the direct radiative perturbation and the climate variability that amplifies or dampens the initial perturbation. Potential climate responses to future eruptions, however, have been rarely studied. Here we show perturbation of Tambora‐size causes significant but no inter‐scenario different global average climate responses, by using Community Earth System Model simulations under preindustrial and RCP8.5 scenarios. Regionally we find severe reduction in African and Asian‐Australian monsoon rainfall and emerge of El Niño‐like responses, largely due to the land‐ocean thermal contrast mechanism. Global warming significantly amplifies such El Niño‐like responses, which feed on the enhanced climatology atmospheric moisture and cause higher sensitivity of monsoon circulation to radiative forcing in the tropics. We also find prolonged Asian‐Australian monsoon suppression associated with the enhanced westerly anomalies over the Pacific, suggesting the complexity of climate responses and feedbacks to external forcing under future climate. Plain Language Summary Climate change often manifests itself as a result of a combination of external drivers and internal variabilities. The episodic eruptive characteristics and strong radiation effects of historical volcanic events provide a powerful tool for studying the response and feedback of internal variabilities to external drivers. In the present study, we use the 1815 eruption of Mt. Tambora as a test case, to simulate and compare the climate responses to Tambora‐size eruption under the preindustrial and RCP8.5 warming conditions. We show how future warming enhances the climate system responses to volcanic perturbation, profoundly in the tropical Indian and Pacific oceans. We demonstrate that the enhanced atmospheric moisture under warming conditions amplifies sensitivity of monsoon circulation to radiative forcing, causing stronger El Niño‐like responses. Key Points Influences of a Tambora‐size eruption on global‐mean climate are found the same in the preindustrial and RCP8.5 warming climate scenarios El Niño responses are found post‐eruption and enhanced under RCP8.5, due to increased moisture and higher sensitivity to monsoon weakening A new perspective on the feedback complexity of internal climate variations and their responses to external forcing under future climate